1995
DOI: 10.1007/bf01276865
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal protective and rescue effects of deprenyl against MPP+ dopaminergic toxicity

Abstract: Intranigral infusion of 1-Methyl-4-phenylpyridinium ion (MPP+, 2.1-16.8 nmol) dose-dependently injured nigral neurons as reflected by reduced dopamine levels in the ipsilateral striatum four days after the infusion of this toxic metabolite of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Coadministration of deprenyl (4.2 nmol) with MPP+ into the substantia nigra protected against MPP(+)-induced moderate (20-50%) but not severe (over 70%) nigral injury as reflected in striatal dopamine reductions. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…Furthermore, increases in endogenous Trx levels seem to correlate with the extent of cellular protection from MPP ϩ -induced apoptosis in primary neuronal cultures of mouse midbrain dopaminergic neurons. These findings are in accord with prior reports that selegiline protects nigrostriatal dopaminergic neurons from oxidative injury caused by MPP ϩ in both in vitro preparations (Mytilineou and Cohen, 1985;Vizuete et al, 1993) and in vivo (Wu et al, 1995). Mytilineou and Cohen (1985) proposed a direct neuroprotective action of selegiline against MPP ϩ -induced neurotoxicity in midbrain dopamine cell cultures.…”
Section: Selegiline Induces Trx Expression That Prevents Mppsupporting
confidence: 81%
See 4 more Smart Citations
“…Furthermore, increases in endogenous Trx levels seem to correlate with the extent of cellular protection from MPP ϩ -induced apoptosis in primary neuronal cultures of mouse midbrain dopaminergic neurons. These findings are in accord with prior reports that selegiline protects nigrostriatal dopaminergic neurons from oxidative injury caused by MPP ϩ in both in vitro preparations (Mytilineou and Cohen, 1985;Vizuete et al, 1993) and in vivo (Wu et al, 1995). Mytilineou and Cohen (1985) proposed a direct neuroprotective action of selegiline against MPP ϩ -induced neurotoxicity in midbrain dopamine cell cultures.…”
Section: Selegiline Induces Trx Expression That Prevents Mppsupporting
confidence: 81%
“…A recent in vivo study indicated that induction of Trx and related pro-survival proteins (superoxide dismutase, catalase, and GSH peroxidase) protect midbrain nigral neurons from MPTP-induced neurotoxicity (Kojima et al, 1999). Our previous in vivo data also indicate that selegiline protects A9 dopaminergic nigral neurons from oxidative injury caused by MPP ϩ , the toxic metabolite of MPTP (Wu et al, 1995). It has been shown to increase levels of reactive oxygen species, such as reactive hydroxyl radicals, which can react with polyunsaturated fatty acids to generate peroxyl lipid radicals, and the related toxic species, malondialdehyde and 4-hydroxy-2,3-nonenal (Chiueh et al, 1994;Rauhala et al, 1998).…”
Section: Induction Of Trx By (؊)-Deprenyl 1411mentioning
confidence: 61%
See 3 more Smart Citations